The Components to Be Considered In The Evaluation of Disability Rate Related to Traffic Accident In The Light of The Supreme Court's Decisions - Kaya, Ahsen; Çelik, Cemil; Aktaş, Ekin Özgür; Güler, Hülya; Şenol, Ender (The Bulletin of Legal Medicine, 2020)
Objective: Traffic accidents can cause liability in terms of both criminal and compensation law. Forensic specialists have a great role in the assessment of permanent sequelae and disability rates associated with these sequelae. In this study, we aimed to evaluate the issues to be taken into consideration by examining the Supreme Court’s decisions of reversals about disability reports related to traffic accidents.Materials and Methods: The decisions were searched in https://karararama.yargitay.gov.tr/YargitayBilgiBankasiIstemciWeb/ by using the concepts of legal regulations which are used in the evaluation of disability rate and “traffic accident” as keywords. The Supreme Court of Decisions of Reversals for disrupting the Decisions about the disability rate reports related to traffic accidents taken by the first-instance courts were researched.Results: 376 Decisions of Reversal of 17th Supreme Court were reached. The issuance of reports according to the statute/regulation which was not in effect at the date of the unjust act was the most frequent (n=262, 69.7%) ground. Then, contradictory rates among the received reports, uncertainty/impenetrability about which statute/regulation is based in the report, spelling errors, not taken a disability report for the basis of the provision and the problems related to the causal link were determined respectively.Conclusion: Disability reports should be understandable, reasoned and in accordance with the relevant legislation. Reports that are not prepared in accordance with the legislation in force, not justified properly, have the problems about causality, conflicting and unsuitable for inspection may cause loss of rights, prolongation of the trial process.
Keywords: Supreme court; decision of reversal; ground; disability report; traffic accident